2019
DOI: 10.3390/met9121342
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size-Dependent Microstructure, Hardness and Electrochemical Corrosion Behavior of Atmospheric Plasma Sprayed NiCrBSi Coatings

Abstract: Particle size is a critical consideration for many powder coating-related industries since it significantly influences the properties of the produced materials. However, the effect of particle size on the characteristics of plasma sprayed NiCrBSi coatings is not well understood. This work investigates the microstructures, hardness and electrochemical corrosion behavior of plasma sprayed NiCrBSi coatings synthesized using different-sized powders. All coatings mainly consist of Ni, N 3 B, CrB, Cr 7 C 3 and Cr 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 72 publications
(101 reference statements)
1
25
0
Order By: Relevance
“…The diffraction profiles were corrected for the instrumental broadening using a corundum sample. Meanwhile, to analyze the influence of ultrasonic assistance on the volume fraction of each phase in the coatings, the following formula was used: [67][68][69] V f ,i ¼ A i…”
Section: Characterizationsmentioning
confidence: 99%
“…The diffraction profiles were corrected for the instrumental broadening using a corundum sample. Meanwhile, to analyze the influence of ultrasonic assistance on the volume fraction of each phase in the coatings, the following formula was used: [67][68][69] V f ,i ¼ A i…”
Section: Characterizationsmentioning
confidence: 99%
“…It can be found in Figure 9A that the Nyquist plots of MAO coatings have different radii of capacitive loops which is related to the charge transfer process. Generally, the capacitive loop has a bigger radius, indicating greater charge transfer resistance and better corrosion resistance of the coatings (Dai et al, 2017;Lei et al, 2018;Sang et al, 2019;Xiang et al, 2020). It can also be obviously found that the coatings fabricated under steps current-decreasing mode show greater radii of the capacitive loop compared with that under the constant current mode.…”
Section: Electrochemical Measurementsmentioning
confidence: 88%
“…Atmospheric plasma spraying of NiCrBSi coatings with two sizes of powder particles (50 to 75 μm and 75 to 100 μm) was investigated in Reference [ 53 ]. By applying powder with smaller particles, a greater coating thickness (598 ± 24 μm) was achieved than the thickness (432 ± 20 μm) obtained by applying powder with larger particles.…”
Section: Statistical Modeling and Different Statistical Methods Inmentioning
confidence: 99%